Standardized Chromatographic and Computational Approaches for Lipophilicity Analysis of Five Gliflozin Antidiabetic Drugs in Relation to Their Biological Activity - Anna Gumieniczek; Anna Berecka-Rycerz; Marcelina Dul; Aleksandra Pryjda (Molecules)
This study represents the first-time experimental analysis of lipophilicity for antidiabetic drugs from the gliflozin class using chromatographic methods alongside computational approaches. The lipophilicity of five gliflozins (canagliflozin (CANA), dapagliflozin (DAPA), empagliflozin (EMPA), ertugliflozin (ERTU), and sotagliflozin (SOTA)) was assessed using RMW and log kW parameters with RP8, RP18, and CN coatings, while methanol and acetonitrile were used as organic modifiers. To enhance the reliability, six reference substances with established lipophilicity values (0.62–3.5) were used for standardization. For computational analyses, the methods ALOGP, iLOGP, MLOGP, SILICOS-IT, WLOGP, XLOGP3, and Consensus. Log P were applied. Descriptive statistics, correlation analyses, and chemometric techniques were employed to compare the results. Experimental lipophilicity values showed strong correlations, indicating that RMW and log kW are reliable parameters for evaluating the lipophilicity of these therapeutically valuable drugs. However, computational lipophilicity values were less consistent, both among themselves and compared to experimental data. Finally, the experimental lipophilicity of gliflozins was analyzed in relation to their pharmacological properties, including protein binding, renal clearance, volume of distribution, half-life, potency (IC50), and lipophilic ligand efficiency (LLE). Our results allow for a confident proposal of a model to experimentally determine the lipophilicity of gliflozin drugs including new derivatives.